The cadence of counterbalance - Biljana Scott, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2009)
This paper explores how political rhetoric draws from poetry. In particular, it focuses on the ‘cadence of counterbalance,’ namely the expression of an antithesis using alliteration. It is suggested that political rhetoric, at its most rousing and memorable, is poetical both because it draws on the musical resources of language and because it appeals to a redressing vision which counterbalances current views of the world with a more desirable one. The cadence of counterbalance is identified as the common denominator of a selection of historical speeches, and is considered to possess the ‘ring of truth’ across centuries, continents and cultures.